Endogenous xenotropic murine leukemia virus-related sequences map to chromosomal regions encoding mouse lymphocyte antigens. - Wejman, J C (1984)
DNAs of all inbred mouse strains contain multiple copies (18 to 28 copies per haploid mouse genome) of endogenous xenotropic murine leukemia virus-related sequences detectable by Southern analysis with a xenotropic murine leukemia virus env gene-specific probe. After PvuII digestion, we identified a subset of xenotropic murine leukemia virus-related sequences that are well resolved by agarose gel electrophoresis and can be mapped to specific chromosomes by using recombinant inbred mouse strains. Interestingly, three of six xenotropic proviral loci that we mapped were integrated near genes encoding mouse lymphocyte antigens (Ly-m22, chromosome 1; Ly-m6, chromosome 2; and Ly-m10, chromosome 19) and a fourth xenotropic proviral locus mapped near a gene on chromosome 4 that has a major influence on xenotropic virus cell surface antigen levels. These studies indicate that xenotropic proviral loci are located on many different mouse chromosomes and may be useful markers for molecularly cloning and characterizing regions of the mouse genome important in lymphocyte development.